The Dynamics of Family Communication and Peer Influence in Adolescent Drug Abuse Experiences: A Case Study at the Subdirectorate of Crisis Mitigation Center (SMCC) - Clara Jelita Gracia Theo; Wiryo Nuryono; Heru Prasetyo; Budi Purwoko; Evi Winingsih (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2026)
Drug abuse among adolescents is a significant social problem that threatens psychosocial development and long-term social functioning. This study aims to explore the dynamics of family communication and peer influence in the drug abuse experiences of a male adolescent undergoing rehabilitation at the Subdirectorate of Crisis Mitigation Center (SMCC), Surabaya. Using a qualitative approach with a single-case study design, data were collected through in-depth semi-structured interviews with the primary participant (H, 17 years old), a rehabilitation counselor assistant, and the participant's biological father, complemented by observation and documentation over a four-month rehabilitation period. Thematic analysis revealed three interconnected themes: suboptimal family communication, characterized by low conversation orientation, the emotional impact of parental divorce, and absence of emotional support; peer influence through behavioral normalization, repeated invitations, direct modeling, and threat of social exclusion; and drug use as a psychological coping mechanism to fill emotional voids and resolve identity confusion during the identity versus role confusion developmental stage (Erikson, 1968). The study contributes a nuanced understanding of how weak family communication and strong peer influence mutually reinforce adolescent vulnerability to drug abuse, integrating Family Communication Patterns Theory (FCPT) with Erikson's psychosocial development theory within a rehabilitation context. Implications for guidance and counseling practice include the application of Gestalt therapy, Acceptance and Commitment Therapy (ACT), family resilience strengthening, and assertive communication training.